Kajian Parameter Lingkungan terhadap Kelimpahan Kepiting Bakau (Scylla sp) di Perairan Muara Semubur Desa Tuik Kabupaten Bangka Barat - halipatul fikri (Akuatik: Jurnal Sumberdaya Perairan, 2020)
Mangrove crab is one of the fishery commoditiesthat has important economic value and is favored by the community because of its delicious meat and high nutritional value. The potential of mangrove crabs in indonesia is quite large, because mangrove crabs have a very wide distribution and can be found almost all over indonesia waters, especially in waters growing up with mangrove forest.This research was conducted in March 2020 in the Semubur estuary, Tuik Village, West Bangka Regency. The data collected consisted of community structure and abundance of mangrove crabs, substrate, and water physics and chemistry parameters. Based on the research results obtained 2 species of crab, Scylla serrate and Pilumnopeusserrativerons. The structure of the mangrove crab community in waters of Semubur estuary, Tuik Village, West Bangka Regency, uniformity index value has an average value of 0,909, where in station I to station IV is classified as high uniformity while station V is classified as moderate uniformity. While the dominance index has an average value of 0,558 where, station I to station IV is classified as moderate dominance while station V is classified as high dominance. The largest abundance of Scylla serrata crabs is 1300 ind / ha found at station I. Meanwhile, Pilumnopeusserratifrons crabs were mostly found at station I with 900 ind / ha. Analysis of the relationship between the abundance of crabs and environmental parameters was analyzed usinganalysis PCA (Principal Component Analysis), where the results of the analysis were that the abundance of crabs was correlated with salinity, sand fraction, dust fraction and water temperature.